Prevalence of canine impaction in the western province of Saudi Arabia: A cross-sectional survey - Dareen Khalid Aljehani (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND/AIM: Canine tooth impaction could have a negative influence on the stomatognathic system and could make it difficult for clinicians to manage malocclusions. The aim of this retrospective study was to investigate the prevalence of canine impaction, which could be a cause of malocclusion, in the population in the western province of Saudi Arabia. METHODS: A retrospective analysis of digital orthopantomograms (OPGs) of 400 patients aged 12-40 years, who are citizens of Saudi Arabia residing in the western province and who presented for treatment at the dental clinics of Batterjee Medical College, Jeddah, Saudi Arabia were included. The OPGs and dental records of these patients were reviewed for canine impaction and were categorized based on age, gender, and type of impaction. RESULTS: The prevalence of patients that exhibited canine impaction was found to be 4%. Males had a significantly higher percentage of prevalence than females (P < 0.016), and impaction was significantly higher among patients aged below 18 years (P < 0.001). Moreover, the most commonly observed impaction was mandibular canine impaction (87.5%). CONCLUSIONS: Prevention of malocclusion and maintenance of a normal dentition (better aesthetics and chewing) necessitates early detection of impacted canines.